PERBANDINGAN HASIL BELAJAR FISIKA ANTARA MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MODEL PEMBELAJARAN INQUIRY KELAS X DI SMA NEGERI 8 LUBUKLINGGAU TAHUN AJARAN 2015/2016 - Tri Ariani; Tria Wulandari (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research entitled "Comparison Between Physics Learning Outcomes Learning Model Problem Based Learning by Inquiry Learning Model Class X SMA Negeri 8 Lubuklinggau In Academic Year 2015/2016". The formulation of the problem is, What is the result of learning physics learning model Problem Based Learning is significantly higher than the class X Inquiry learning models in SMA 8 Lubuklinggau 2015/2016 Academic Year?. This study aims to determine whether the results of studying physics using Problem Based Learning teaching model is significantly higher than the results of studying physics using Inquiry learning model class X SMA Negeri 8 Lubuklinggau Academic Year 2015/2016. The research method used was experimental method to the type of comparison. The population is all students of class X SMA 8 Lubuklinggau Academic Year 2015/2016 and as the sample is X.1 classes totaling 23 students and X.2 classes totaling 25 students and drawn at random. Data collected by the testing techniques. Data were analyzed using t-test at the significant level Î± = 0.05. Based on the results of data analysis can be concluded that "learning outcomes of students who take physics learning using learning model Problem Based Learning is significantly higher than the learning outcomes of students who take physics learning using learning model Inquiry class X SMA Negeri 8 Lubuklinggau". The average value of the end of the first experimental group after treated with learning model Problem Based Learning at 73.30 and the experimental class II Inquiry learning model at 66.04. Keywords: Problem Based Learning, Inquiry, Learning Outcomes.